In the realm of Vatnajökull a companion on the Southern Ring Road - Helgi Björnsson 1942-; Þóra Ellen Þórhallsdóttir 1954- (Mál og menning, 2021)
his book takes you through the region south of Vatnajökull. It is Iceland’s most dynamic part and here its natural contrasts are particularly well displayed: lush vegetation and barren deserts, wide plains and high mountains, green grasslands, black sands and white glacier ice. The authors are Helgi Björnsson, a world-renowned glaciologist and emeritus research professor at the University of Iceland, and Þóra Ellen Þórhallsdóttir, professor of botany at the University of Iceland.
Keywords: Vatnajökull